2011
DOI: 10.1007/s11302-011-9266-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profile of GTP-mediated differentiation of C2C12 skeletal muscle cells

Abstract: Several purine receptors have been localised on skeletal muscle membranes. Previous data support the hypothesis that extracellular guanosine 5′-triphosphate (GTP) is an important regulatory factor in the development and function of muscle tissue. We have previously described specific extracellular binding sites for GTP on the plasma membrane of mouse skeletal muscle (C2C12) cells. Extracellular GTP induces an increase in intracellular Ca 2+ concentrations that results in membrane hyperpolarisation through Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…These findings provided the basis for further understanding of the role of the JAK-STAT pathway in myogenic differentiation. In addition, among transcriptional profile of GTP (guanosine 5′-triphosphate)-mediated differentiation of C2C12 myoblasts, genes such as interleukin 6, Pim-1 and IL1Ra (interleukin 1 receptor antagonist homolog 1) are upregulated, and it is suggested that JAK-STAT pathway can play a crucial role in myogenic differentiation 43 . In next section, we will focus on the role of the JAK-STAT pathway in the differentiation and proliferation of skeletal muscle myoblasts.…”
Section: Jaks-stats Pathway In Myogenic Differentiationmentioning
confidence: 99%
“…These findings provided the basis for further understanding of the role of the JAK-STAT pathway in myogenic differentiation. In addition, among transcriptional profile of GTP (guanosine 5′-triphosphate)-mediated differentiation of C2C12 myoblasts, genes such as interleukin 6, Pim-1 and IL1Ra (interleukin 1 receptor antagonist homolog 1) are upregulated, and it is suggested that JAK-STAT pathway can play a crucial role in myogenic differentiation 43 . In next section, we will focus on the role of the JAK-STAT pathway in the differentiation and proliferation of skeletal muscle myoblasts.…”
Section: Jaks-stats Pathway In Myogenic Differentiationmentioning
confidence: 99%
“…More recently, it has been shown that in the early stages of differentiation, GTP regulates many genes specifically involved in myogenesis including Pp3ca, Gsk3b and Pax7. This indicates a possible function for the nucleotide as a differentiation regulator in these cells [48].…”
Section: The Effects Of Gbps In Muscle Cellsmentioning
confidence: 82%
“…2 ). Calcium homeostasis appeared to be important in the maintenance of mechanisms promoting the expression of muscle-specific proteins and myoblast fusion (Mancinelli et al 2012 ). Another pathway enriched by differentially expressed genes in palmitate-treated myoblasts is Wnt signaling, which is important for early development and commitment of myogenic cells (Otto et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%